A Case of Reed's Syndrome: An Underdiagnosed Tumor Disorder - Georgios Kontochristopoulos; Anargyros Kouris; Evgenia Balamoti; Charitomeni Vavouli; Vasiliki Markantoni; Elefteria Christofidou; Christina Antoniou (Karger Publishers, 2014)
Cutaneous leiomyomas are uncommon, benign smooth muscle tumors originating from the arrector pili muscle of the hair follicle that are frequently unrecognized and underdiagnosed by clinicians. They sometimes coexist with common uterine fibroids in an inherited disorder named multiple cutaneous and uterine leiomyomatosis, also referred to as Reed's syndrome. We report a case of Reed's syndrome in a young woman who had been misdiagnosed for many years.